SULT2B1b inhibits reverse cholesterol transport and promotes cholesterol accumulation and inflammation in lymphocytes from AMI patients with low LDL-C levels. (29th January 2020) - Zhang, Yanan; Guo, Zhongzhou; Wu, Tongwei; Liu, Jichen; Zhang, Bin; Lai, Wenyan; Tu, Wenwei; Guo, Zhigang; Luo, Tiantian
Abstract: The current main treatment for coronary artery disease (CAD) is to reduce low-density lipoprotein cholesterol (LDL-C) by statins, which could decrease the incidence of major adverse cardiovascular events (MACEs) by 30%. However, many residual risks still remain. To clarify the mechanism involved, we studied patients with acute myocardial infarction (AMI) with low LDL-C levels. Lymphocytes were isolated, and it was found that despite no difference in plasma LDL-C level, the lymphocyte cholesterol content was higher in AMI patient than those in non-CAD patients; thus, the decrease in intracellular cholesterol content was inconsistent with that in the plasma. Additionally, [ 3 H]-cholesterol efflux rates were lower and mRNA levels of the inflammatory factors tumour necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) higher in AMI lymphocytes. It was found that sulphotransferase 2B1b (SULT2B1b) expression was higher in AMI lymphocytes. Further research using Jurkat T lymphocytes confirmed that SULT2B1b knockdown increased cholesterol efflux capacity and decreased mRNA levels of TNF-α and IFN-γ by increasing liver X receptor (LXR)-β levels. Furthermore, the degree of CpG island methylation in the SULT2B1b promoter was reduced in cells from AMI patients. In conclusion, SULT2B1b up-regulation due to hypomethylation of its promoter promotes cholesterol accumulation and inflammation by inhibiting LXR-β in lymphocytes of AMI patients with low LDL-C levels. Therefore, reducing intracellular cholesterol is also important as plasma cholesterol levels. Therapeutic approaches to decrease SULT2B1b expression might be potentially beneficial for CAD prevention by decreasing intracellular cholesterol.